Analysis of Scientific Educational Game Tools Implementation for Early Childhood Students in West Nusa Tenggara - Baik Nilawati Astini; Gunawan Gunawan; Ni Luh Putu Nina Sriwarthini Sriwarthini (Postgraduate, University of Mataram, 2023)
This qualitative descriptive study aims to determine the implementation of scientific educational game tools for early childhood in West Nusa Tenggara. Samples were taken using a simple random method from 3 districts in West Nusa Tenggara, which are North Lombok, East Lombok, and West Sumbawa. Data were collected using a questionnaire form. The research data were analyzed using a qualitative descriptive method. The results of this research illustrate the implementation of scientific educational game tools for early childhood in the West Nusa Tenggara province. Based on the data obtained, as many as 14 scientific educational game tools have been found and are suitable for science learning in early childhood. There are 11 types of indoor scientific educational game tools that can be used to stimulate science learning in early childhood and as many as 3 types of outdoor scientific educational game tools that can be used to stimulate science learning in early childhood. The implementation of scientific educational game tools that are in accordance with the science concept is only 28% and was categorized as low. This shows that the teacher's understanding and competency in teaching science with the help of scientific educational game tools is still limited